2019
DOI: 10.1186/s12882-018-1171-3
|View full text |Cite
|
Sign up to set email alerts
|

Validation of diagnostic utility of fasting plasma glucose and HbA1c in stable renal transplant recipients one year after transplantation

Abstract: BackgroundThe use of HbA1c ≥6.5% for diagnosis of diabetes has been challenged for post-transplantation diabetes mellitus (PTDM) also known as new onset diabetes after transplantation (NODAT) due to a low sensitivity early after renal transplantation. PTDM diagnosed with an oral glucose tolerance test (OGTT) is highly predictable for long-term patient mortality. HbA1c was introduced for diagnosis based on the risk of developing diabetic retinopathy. The utility of HbA1c measures versus glucose criteria has not… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
20
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(24 citation statements)
references
References 13 publications
4
20
0
Order By: Relevance
“…In a retrospective analysis of nearly 500 KTRs without known diabetes who underwent comprehensive assessment of glycaemic status at one year after transplant, including HbA1c, FPG and OGTT, using HbA1c alone (!6.5% or 48 mmol/mol) resulted in a specificity of 97% and sensitivity of 43% [32]. This finding is in line with those of a systematic review and metanalysis showing that HbA1c !…”
Section: Screening For Post Transplant Diabetes Mellitus (Ptdm)supporting
confidence: 89%
“…In a retrospective analysis of nearly 500 KTRs without known diabetes who underwent comprehensive assessment of glycaemic status at one year after transplant, including HbA1c, FPG and OGTT, using HbA1c alone (!6.5% or 48 mmol/mol) resulted in a specificity of 97% and sensitivity of 43% [32]. This finding is in line with those of a systematic review and metanalysis showing that HbA1c !…”
Section: Screening For Post Transplant Diabetes Mellitus (Ptdm)supporting
confidence: 89%
“…Furthermore, it is known that oral glucose tolerance tests (OGTTs) are the gold standard diagnostic tool to diagnose PTDM. Unfortunately, OGTTs were not performed, but recently it has been shown that the combined use of fasting plasma glucose and HbA1c criteria appears to be a diagnostic strategy for PTDM in stable renal transplant recipients [72]. Another limitation of this study is that only 38 subjects developed PTDM during follow-up, which led to a lack of power.…”
Section: Discussionmentioning
confidence: 93%
“…This multicenter study is likely more generalizable than many prior single-center studies (Supplementary Table 1). 2,3,[9][10][11]13,15,[20][21][36][37][38][39][40][41][42][43][44][45][46][47] Many studies defined PTDM using the 2003 International Consensus Guidelines based on recommendations of the ADA. 18 Some groups also used extended PTDM diagnostic criteria that include administration of antihyperglycemic agents and updated ADA recommendations such as hemoglobin A1c ≥6.5%.…”
Section: Discussionmentioning
confidence: 99%
“…For the PTDM group, event rates per 1000 patient-years were as follows: dcGF 32 (95% CI: 21-47), aGF 67 (51-88), and all-cause mortality 43 . Event rates for the non-PTDM group were: dcGF 37 (30)(31)(32)(33)(34)(35)(36)(37)(38)(39)(40)(41)(42)(43)(44)(45)(46), aGF 58 (49-68), and all-cause mortality 28 (22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32)(33)(34)(35). Results were unchanged when considering diabetes treatment type (insulin therapy, oral antihyperglycemics, and diet only) for the PTDM patients.…”
Section: Association Of Ptdm and Adverse Graft Outcomesmentioning
confidence: 99%